Ab initio molecular dynamics study of intersystem crossing dynamics for MH2 (M = Si, Ge, Sn, Pb) on spin-pure and spin-mixed potential energy surfaces - Wada, Satoi (Journal of computational chemistry, 2024)
© 2023 Wiley Periodicals LLC.